2021
DOI: 10.3389/fphys.2021.603910
|View full text |Cite
|
Sign up to set email alerts
|

New Insights Into the Regulation of Lipoprotein Metabolism by PCSK9: Lessons From Stable Isotope Tracer Studies in Human Subjects

Abstract: Proprotein convertase subtilisin/kexin type 9 (PCSK9) is a convertase enzyme mostly produced by the liver. It is a key regulator of LDL metabolism because of its ability to enhance degradation of the LDL receptor. PCSK9 also regulates the metabolism of lipoprotein(a) [Lp(a)] and triglyceride-rich lipoproteins (TRLs). Its key role in modulating atherosclerotic cardiovascular disease (ASCVD) is supported by genetic studies and clinical outcome trials. Kinetic studies provide mechanistic insight into the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…( 45 ) Supporting these observations, PCSK9 inhibitors reduce circulating Lp(a). ( 46 ) However, the effect of the PCSK9 rs7552841 mutation on Lp(a) did not translate to significant protection against fibrosis onset in our cohort and in the UKBBC (data not shown).…”
Section: Discussionmentioning
confidence: 57%
“…( 45 ) Supporting these observations, PCSK9 inhibitors reduce circulating Lp(a). ( 46 ) However, the effect of the PCSK9 rs7552841 mutation on Lp(a) did not translate to significant protection against fibrosis onset in our cohort and in the UKBBC (data not shown).…”
Section: Discussionmentioning
confidence: 57%
“…These PCSK9 inhibitors are used to treat primary hyperlipidemia and have been found to reduce myocardial infarction and stroke in persons with established CVD [ 227 , 228 ]. The PCSK9 enzyme enhances degradation of the LDL receptor; therefore, its inhibition allows for greater accumulation of this receptor, enhancing clearance of apoB-containing lipoproteins and reducing the LDL and apoB particle number [ 229 , 230 ]. It has been suggested that if the target LDL-C level is not achieved with the maximum tolerated statin dose, the next adjunctive therapy to add after ezetimibe would be a PCSK9 inhibitor [ 231 , 232 ].…”
Section: Apob As a Target Of Cvd Treatmentmentioning
confidence: 99%
“…Statins increase the activity of LDLRs, thus increasing the catabolism of VLDL, LDL and intermediate-density lipoprotein (IDL). Furthermore, statins also decrease the hepatic and endogenous cholesterol production by inhibiting HMG-CoA reductase [43], but they do not affect Lp(a) [145]. Interestingly, it could be demonstrated that statins also have some detrimental effects, for example by increasing the levels of circulating PCSK9 [146].…”
Section: Pcsk9 Activators/inhibitorsmentioning
confidence: 99%
“…They act on the PCSK9 protein itself rather than targeting the gene expression. Additionally, PCSK9 mAb decreases the production rate of hepatic Lp(a) particles [145] on top of increasing the clearance of them [78]. Thus, the use of mAbs have been highly sought out for the treatment of cardiovascular complications.…”
Section: Pcsk9 Activators/inhibitorsmentioning
confidence: 99%